Tools for worm experimentation on the DETER testbed. (6th July 2010) - Wei, Songjie; Hussain, Alefiya; Mirkovic, Jelena; Ko, Calvin
Worm experimentation is challenging for researchers today because of the lack of standardised tools to simulate and emulate worm spreads in a realistic setting. We have developed two tools for the DETER testbed to aid in worm experimentation: the PAWS simulator for internet-wide worm propagation studies and the WE emulator for analysis of worm spread and defence strategies in local area networks. We evaluate performance and fidelity of our tools by replicating results from recently published research. Both tools can be easily configured as per user specifications, facilitate comparison with past research and reduce the barrier to entry for worm researchers.